2020
DOI: 10.1016/j.ijleo.2019.163122
|View full text |Cite
|
Sign up to set email alerts
|

A novel filter wheel for multi-channel switching and polarization rotation

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…It can be concluded from Table 2 that the SMs were used to realize the light filtering and focusing function, and the direct drive-type PZT actuators were mainly used to realize the focusing function. Generally speaking, SM needs to be equipped with the transmission mechanism to achieve rotary motion to switch filter plates, which brings complex structural design and heavyweight to MSCs, [48,49] SMA is characterized by its remarkable deformation and recoverability. Recent studies have shown that SMAs can effectively be used as actuators through suitable and dedicated mechatronic design.…”
Section: Demonstration Of Integrated Light Filtering and Focusing Fun...mentioning
confidence: 99%
“…It can be concluded from Table 2 that the SMs were used to realize the light filtering and focusing function, and the direct drive-type PZT actuators were mainly used to realize the focusing function. Generally speaking, SM needs to be equipped with the transmission mechanism to achieve rotary motion to switch filter plates, which brings complex structural design and heavyweight to MSCs, [48,49] SMA is characterized by its remarkable deformation and recoverability. Recent studies have shown that SMAs can effectively be used as actuators through suitable and dedicated mechatronic design.…”
Section: Demonstration Of Integrated Light Filtering and Focusing Fun...mentioning
confidence: 99%